Recent Advances in Synthetic Methodologies to Form C-18F Bonds - Liu, Zhiyi; Sun, Yijun; Liu, Tianfei (Frontiers in Chemistry, 2022)
Positron emission tomography (PET) is an important technique for the early diagnosis of disease. Due to the specific physical and chemical properties of Fluorine-18, this important isotope is widely used in PET for labelling and molecular imaging, and its introduction into medicine molecules could produce PET tracers. Developing with the development of organic synthetic methodologies, the introduction of Fluorine-18 into drug molecules efficiently and rapidly under mild conditions, and the formation of C-18F chemical bonds, has become one of the leading topics in both organic synthetic chemistry and radiochemistry. In this mini-review, we review a series of recent advances in the organic synthesis of C-18F bonds (2015-2021), including non-catalytic radiofluorinations via good leaving functional groups, transition metal-catalyzed radiofluorinations, and photo- or electro-catalytic synthetic radiofluorinations. As a result of the remarkable advancements in this field, organic synthetic methods for forming C-18F bonds are expected to continue to grow.